Pengaruh Harga,Kualitas Produk,dan Fitur Aplikasi Terhadap Niat Pembelian Ulang di TikTok Shop ( Pada Mahasiswa Universitas Cipasung) - nabilaazizah Dwi Putri; Isyana Rahayu (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The rapid development of e-commerce has changed consumer behavior in conducting online transactions. One platform that has experienced significant growth is TikTok Shop, which integrates social media and shopping activities into a single application. The high use of TikTok Shop among university students indicates changes in consumption patterns influenced by factors such as price, product quality, and application features. In addition, differences in previous research findings regarding factors influencing repurchase intention indicate the need for further research. This study aims to analyze the effect of price, product quality, and application features on repurchase intention among TikTok Shop users at Universitas Cipasung Tasikmalaya. This study employed a quantitative associative method with a sample of 105 respondents determined using the Slovin formula. Data were collected through questionnaires using a 1–5 Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results showed that price, product quality, and application features have a positive and significant effect on repurchase intention. The findings indicate that price suitability, good product quality, and ease of application use increase consumers' intention to make repeat purchases. These results suggest that improving marketing strategies and service management on the platform can support customer satisfaction and encourage sustainable customer loyalty.